Strengthening women’s resilience and participation in climate governance in the agrifood sector through public policies: A strategic review of literature - Mohammed, Kamaldeen; Najjar, Dina; Bryan, Elizabeth (Taylor and Francis, 2026)
Women are uniquely vulnerable to climate change but play a critical role in enhancing the climate resilience of the agrifood sector. Based on a rapid review of academic and grey literature, this paper synthesizes the state of knowledge on the level of integration of gender aspects in climate change policies and women’s involvement in policy processes in the Global South. It examines women’s participation in climate change governance, strategies for enhancing this participation, and policy approaches to strengthen women’s resilience while addressing gender inequalities. Findings show that public policies often employ quotas, incentives, and capacity building initiatives to boost women’s participation in governance. However, meaningful engagement in higher-level decision-making remains limited, with quotas sometimes resulting in superficial involvement. Facilitating women’s access to agrifood resources, human capital, and economic opportunities, as well as addressing harmful gender norms, are identified as effective strategies to build resilience. Despite these promising approaches, gaps remain in the implementation and evaluation of policies aimed at enhancing women’s resilience and participation. The paper concludes by recommending outcome-oriented research and robust evaluations of public policy effectiveness in improving women’s climate resilience and governance roles.